KETAHANAN PANGAN RUMAH TANGGA TANI PERKOTAAN DAN PERDESAAAN KABUPATEN GUNUNGKIDUL - , DYAH AYU WIDYANITHA, Dr. Ir. Suhatmini Hardyastuti, SU. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research is conducted (1) to analyze share of farm household food expenditure for the urban and rural, (2) to analyze the level of urban and ruralenergy farm household, (3) to analyze the level of household food security urban and rural farm, (4) to analyze desirable dietary pattern of urban and rural farm household, (5) to understand influencing factor of score food security farm household. The primary method for this research use descriptive analysis, sampling is done by using simple random method with 25 urban and 25 rural farm household in Gunungkidul. The data was analyzed by independent sample t-test and multiplier regression analysis by Ordinary Least Square (OLS). The results showed that (1) the share of farm household food expenditure in urban areas is lower than the share of food expenditure of farm households in rural areas, (2) the adequacy of farm household energy in rural areas is higher than the farm households in urban area,(3) urban households food secure 20%, vulnerable food40%,less food 12%, food insecurity 28%, yet rural household food secure 16%, vulnerable food 48%, less food 4%, food insecurity 32%, (4) food pattern expectations farm households in urban areas are not higher than the expectation of food patterns in rural areas, (5) factors that positively affect the food security of farm households are farm household income and location (urban and rural).